"Fractured Light": From Globalization's Hyper-Illumination to Culture as Symbolic Exchange. Issue 7 (3rd October 2017) - Prentice, Chris
Abstract : This essay argues epistemic reduction and reification of indigenous cultures in imperial and colonial discourse underlies the fundamentally economic terms of representation of those cultures. The pursuit of cultural knowledge and forms of cultural exhibition for instrumental, including commercial, ends entails such reduction of culture to representation. Cultural self-representation changes the relations of producer and consumer in economic exchange, but does not change its essentially reductive notion of culture. With contemporary neoliberal globalization, agency, within market relations – like self-representation in a representational economy – ultimately risks assimilation to the global market in cultural difference. Two novels by Māori writers, Paula Morris's Rangatira (2011) and James George's Ocean Roads (2006), point to contemporary commodification and consumption of indigenous cultural difference as the apotheosis of processes of cultural objectification, reification and commodification that began with imperial colonialism. While Rangatira is set largely between the 1860s and 1890s, and Ocean Roads between 1945 and 1989, both are published within the era of contemporary neoliberal globalization, and ultimately concern the critical stakes in relation to cultural decolonization. They contextualize the epistemic and genocidal violence that has been given an alibi in the valorization of (self-)representational images and performances. In refusing to objectify Māori culture – or by disarticulating such objectifications – the novels point to the potential for those un/signified spaces to evoke precisely the importance of culture as dynamic, unframeable "symbolic exchange". I argue aspects of Baudrillard's critical notion of "symbolic exchange" reveal both the stakes and the possibilities of (re)conceiving culture outside of market relations.